Degradation Kinetics of MEA and DEA by Fenton’s Reagent with Biological Post-Treatment - Harimurti, Sabtanti Harimurti (2009)
Alkanolamines in aqueous solutions are commonly used for scrubbing of carbon dioxide from natural gas, synthesis gas and other gas mixtures. Large quantities of amines appear in the wastewater during cleaning and maintenance as well as shutdown of the absorption and desorption columns. The amines are not readily biodegradable and such wastewater cannot be treated in the conventional treatment facility. Advanced Oxidation Processes (AOP), such as oxidation by Fenton’s reagent, UV-H2O2 and UV-Ozone offer a class of techniques of treatment or partial degradation of recalcitrant organics which are not readily amenable to conventional biological oxidation. Degradation of alkanolamines by Fenton’s reagent has been investigated in this work. Mono- and di-ethanolamines have been selected as two model alkanolamines. Fenton’s oxidation experiments were conducted in a jacketed glass reactor and the effects of process parameters such as dosing of the reagents (H2O2 and FeSO4;7H2O), pH, initial concentration of the amine as well as the mode of addition of the reagents have been studied in details. Since the degradation process involves a number of intermediates, not all of which could be identified, the chemical oxidation demand (COD) of the amine solution is selected as a measure of the extent of degradation. Determination of the COD was done by Hach 5000 spectrophotometer following the standard procedure. FTIR Spectrometer and HPLC were used for identification and analysis of the degradation fragments. Amine concentrations upto 20,000 ppm was used since it is characteristic of the effluents from a natural gas treating plant. It was observed that only a fraction of the COD could be removed by using a moderate quantity of the reagents. Also, for a solution having a higher initial amine concentration, the degradation process was very fast. Most of the total COD removal was attained within a few minutes from the start of the reaction. This was followed by a very slow rate of COD removal. The reaction rate as well as the extent of reaction was most favored at a pH of 3. Also the rate of degradation passes through a maximum with increase of H2O2 dosing and the Fe2+/H2O2 ratio. Continuous addition of the Fenton’s reagent is much more effective with better utilization of the H2O2 than one-time addition. Besides COD, time evolution of the concentrations of the amine and hydrogen peroxide were measured to monitor the course of the reaction. A rapid fall of H2O2 concentration accompanied the fast COD reduction. But COD removal was less steep for continuous reagent addition experiments. The trends were very much similar for both MEA and DEA. They showed closely similar behavior. Although it was not possible to identify all the degradation products of the amines, the formation of glycine as one of the intermediates was decisively established. This indicates that the alcohol group of an alkanolamine might be more vulnerable to electrophilic attack by the HO• radicals than the α-carbon atom with respect to the alcohol group. A plausible reaction pathway is suggested and a rate equation for MEA degradation was developed. A high dose of Fenton’s reagent was not of help to increase the COD reduction. With addition of the stoichiometric quantities of the regent, the degradation amounted to only about 60% COD removal even though about 98% of H2O2 as hydroxyl radical source was utilized. Oxidation of one of the degradation products namely glycine using Fenton’s oxidation was investigated separately. The degradation rate was slower than the pure substrate. Since 40-50% of the COD remains in the Fenton-treated solution, we explored the biodegradability of the organic fragments and oxidation products. The biodegradability test was carried out in an aerobic batch reactor prescribed by the materials and methods specifications in the Zahn- Wellens/EMPA Test according to the US Environmental Protection Agency (EPA) method OPPTS 835.3200. Partially degraded alkanolamines after about 40% COD removal by Fenton’s oxidation was used to study the biodegradability. The biological oxidation of untreated alkanolamine was done in parallel. The COD in solution as well as the biomass concentration was monitored to follow the course of the reaction. The pH of the medium ranged between 6.5 – 8. No attempt to maintain a constant pH by buffering was made in order to ascertain the usefulness of the method under industrial operating conditions. ‘Activated sludge’ from the central wastewater treatment unit of this university was used for seeding the batch bioreactor. The results show that the acclimatization time for biological oxidation of a partially degraded amine sample was about the half of that of the ‘pure’ amine. The time of maximum COD removal was also shorter for the former sample. The kinetics of biomass growth could be fitted by the Monod equation. The kinetic constants were evaluated. Emission of ammonia from the reactor was detected and an ammonia probe was used to monitor the formation of ammonia during the biodegradation process. It appears that ammonia formation per unit COD of the partially degraded sample was more than that of a ‘pure’ amine. This observation is compatible with the formation of more oxygenated degradation products such as amino-acids during Fenton’s oxidation. The results of this study are expected to be useful for developing a practical strategy of treatment of amine-laden wastewater in natural gas-treating plants.